2008
DOI: 10.5664/jcsm.27238
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Pattern Differences Between Older Adult Dementia Caregivers and Older Adult Noncaregivers Using Objective and Subjective Measures

Abstract: ScieNtific iNveStigAtioNSStudy objectives: Informal caregivers of persons with dementia often complain about poor quality sleep; however, studies on caregivers have mixed results when examining sleep values. The purpose of this study was to describe the sleep patterns in a subset of dementia caregivers who provide care during the night, and compare those patterns to noncaregiving adults. Methods: Data from a study on dementia caregivers and from a study of sleep in older adults were used. Both studies used obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 38 publications
10
81
6
Order By: Relevance
“…Dissimilarly, in our study, the average sleep onset latency was longer than in previous studies. 9,45,46 Given the Approximately 67% of caregivers reported the use of sleep medications at least once during the past month. This rate is higher than rates reported in other sleep studies that found that the rates of sleep medication use in caregivers ranged from 38 to 42%.…”
Section: Multiple Regression Analysis Results For Subjective and Objementioning
confidence: 99%
See 1 more Smart Citation
“…Dissimilarly, in our study, the average sleep onset latency was longer than in previous studies. 9,45,46 Given the Approximately 67% of caregivers reported the use of sleep medications at least once during the past month. This rate is higher than rates reported in other sleep studies that found that the rates of sleep medication use in caregivers ranged from 38 to 42%.…”
Section: Multiple Regression Analysis Results For Subjective and Objementioning
confidence: 99%
“…First, symptoms of depression commonly experienced by caregivers are associated with disruptions in sleep. 5,8,9 Second, it is well established that individuals with dementia commonly experience sleep disruptions, and these disruptions are viewed as problematic by caregivers. 5,8 Finally, these factors could interact to form a self-perpetuating cycle of sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven studies in our review included an agematched non-caregiver or/and a non-Alzheimer's caregiver comparison group to further examine sleep differences. Seven of them concluded that family caregivers had more disturbed sleep than non-caregivers (Cupidi et al, 2012;Lee, 2008;McKibbin et al, 2005;Mills et al, 2009;Rowe et al, 2008;von Kanel et al, 2010;Willette-Murphy et al, 2006), while the other four studies did not find a significant difference in sleep between groups. In the study conducted by Castro et al (2009), family caregivers reported having more symptoms of sleep disturbances than non-caregivers.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Two studies examined differences between caregiver and non-caregiver groups on daytime sleepiness, which indicates whether a person is obtaining adequate sleep or needs to improve sleep hygiene (Castro et al, 2009;Rowe et al, 2008). Daytime sleepiness was significantly higher in caregivers than non-caregivers (Rowe et al, 2008). Castro et al also found that caregivers' daytime sleepiness (ESS: 8.3 Ϯ 5.3) was higher than that of non-caregivers (ESS: 6.8 Ϯ 3.4); however, the difference was not statistically significant.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…The use of actigraphy in this project has been described elsewhere (Rowe, McCrae, Campbell, Benito, & Cheng, 2008). In summary, bedtime and out-of-bed were generally set by using the times listed in the caregiver's sleep diary.…”
Section: Objective Sleepmentioning
confidence: 99%